Pengaruh Radiasi UV Buatan Terhadap Kerusakan Permukaan Bahan Isolasi Resin Epoksi Silane - Yanolanda Suzantry H; Suharyanto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
Polymer is now developed as the material replacement of the porcelain isolator and glass insulators. However, tropical climates and high rainfall can cause problems to its. Ultraviolet radiation will continuously accelerate to the surface of the polymer insulator material. As a result, the surface of the insulating material becomes easier letting electric current flow and a fast formation of extensive damage to the surface of the insulator material. Materials used in this study were made from epoxy resin diglycidyl ether of bisphenol-A (DGEBA) as the base material, metaphenylen diamine (MPDA) as the reinforcement material and silica sand. DGEBA and MPDA composition was 30% silica sand filler 30%, 25%, 20%, 15%, 10% and 10% silicone rubber was 15%, 20%, 25%, 30%. The size of the test material was 120 mm x 50 mm x 5 mm. The study was conducted in the laboratory according to standard IEC 587: 1984. This study was conducted to determine the effect of ultraviolet radiation on hydrophobic contact angle and surface damage on the broad value of insulation material epoxy resin silanes. The results showed that the length of exposure time to UV light tended to increase the value of the contact angle. This was due to exposure to artificial UV rays which would accelerate the degradation process. The longer the level of ultraviolet radiation on the sample accelerating the degradation off silane epoxy resin insulators in addition, it caused greater leakage current on extensive damage to the surface of the insulating material.